Exploring worker consciousness in China. (2nd July 2016) - Leung, Elly; Caspersz, Donella
ABSTRACT: This paper presents findings from a study that has explored how the lived experience of everyday Chinese workers influenced their struggle to improve their working conditions. We argue that because the consciousness of everyday Chinese workers remains at an embryonic level, their ability to campaign and change their working conditions remains constrained. We inform this argument by engaging with Foucault's power–knowledge framework (1980). The study draws on original interviews with n  = 74 Chinese workers gathered across two phases of data collection conducted between 2011 and 2014.